2022
DOI: 10.1111/acem.14636
|View full text |Cite
|
Sign up to set email alerts
|

The use of dexmedetomidine in the emergency department: A systematic review

Abstract: Sedatives, anxiolytics, and analgesics are near-ubiquitous interventions during daily care in the emergency department (ED). The agents most commonly used to treat intubated patients include sedatives acting on the gamma-aminobutyric acid (GABA) receptor, such as benzodiazepines and propofol, as well as the opioid analgesic fentanyl. Benzodiazepines are highly deliriogenic 1 and may prolong duration of mechanical ventilation and length of stay. 2 Propofol can be associated with significant hypotension and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 62 publications
(191 reference statements)
1
13
0
Order By: Relevance
“…Larger observational studies will be required to more precisely define and characterize the risk of these events. Our results are generally consistent with previous safety data in the ED setting, 11 although definitions of HAEs in previous work have been inconsistent and many previous ED‐based studies have not specifically reported safety data. Direct comparison with large ICU‐based clinical trials is problematic due to varying definitions of HAE and the difference in populations studied.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Larger observational studies will be required to more precisely define and characterize the risk of these events. Our results are generally consistent with previous safety data in the ED setting, 11 although definitions of HAEs in previous work have been inconsistent and many previous ED‐based studies have not specifically reported safety data. Direct comparison with large ICU‐based clinical trials is problematic due to varying definitions of HAE and the difference in populations studied.…”
Section: Discussionsupporting
confidence: 91%
“…A sample size calculation was not performed a priori because the primary analysis was descriptive and focused on characterization of DEX use in the ED and clinician perceptions of DEX. Based on previous data, 11,12 our sample size was recognized as likely to be adequate for investigation of ED DEX use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations